Intelligent Irrigation System Based on Raspberry Pi and Artificial Intelligence Vision - Yu, Mingyu; Zheng, Xiaoxia (International Journal of Advanced AI Applications, 2025)
In today's fast-paced life, people are often too busy with work to water their houseplants in a timely manner, which not only affects the growth and development of plants but also reduces their survival rate. Aiming at the shortcomings of traditional watering methods and existing automatic watering devices, as well as people's demand for further improving the intelligence and automation of watering equipment, this paper designs an automatic irrigation system by combining soil moisture sensors and OpenCV visual recognition. The system uses a Raspberry Pi 4B single-chip microcomputer as the control core, which can monitor the soil moisture of flowers in real-time. The monitored data is transmitted to the CPU module. When the moisture is lower than the set threshold, the single-chip microcomputer starts the water pump to pump water, realizing the function of automatic flower watering. For different water requirements of various plants, the starting threshold can be manually adjusted, making the system flexible and reliable in operation and having certain popularization value.